Fear of childbirth among pregnant women in Eastern Ethiopia: A community-based study. (January 2023) - Dereje, Adisalem; Dheresa, Merga; Desalew, Assefa; Tura, Abera Kenay
Abstract: Introduction: Fear of childbirth refers to feelings of uncertainty and anxiety before, during, or after childbirth by thinking about future labor and birth or experience of others. Evidence on burden of fear of childbirth and its associated factors is limited in Ethiopia. In this study, we assessed magnitude of fear of childbirth and its associated factors among pregnant women in Eastern Ethiopia. Methods: A community-based cross-sectional study was conducted among randomly selected pregnant women recruited from Kersa Health and Demographic Surveillance System—an open cohort consisting of continuous registry of health and demographic conditions in eastern Ethiopia. Women were interviewed and fear of childbirth was assessed using the Wijma Delivery Expectancy Questionnaire. Data were entered using EpiData 3.1 and analyzed using SPSS 20. Factors associated with fear of childbirth were identified using binary and multiple logistic regression and described using adjusted odds ratio (aOR) along with 95% confidence interval (CI). Finally, statistical significance was set at p < 0.05 in the multiple logistic regression. Results: Of a total of 476 pregnant women included in the study, 111(23.3%; 95% CI 19.3-26.9) had fear of childbirth. Fear of childbirth was more likely among women who had no antenatal care (aOR = 2.6; 95% CI:1.22-5.50), no husband support (aOR = 5.7; 95% CI: 2.32-13.10), unplanned pregnancy (aOR = 7.8; 95% CI: 3.92-15.42), and had history of complication in labor and pregnancy (aOR = 10.4; 95% CI: 5.20-20.81). Conclusion: A quarter of pregnant women in eastern Ethiopia had fear of childbirth. Helping women to have positive pregnancy experience requires strengthening antenatal care, partner support, and prevention of unwanted pregnancy.